Criatividade em rede: uma análise comparativa do modelo de gestão de lojas colaborativas de três cidades do Brasil - Watanabe, Jefferson Yuji (2023)
The field of creative economy emerges as an alternative for economic development to countries in a context of de-industrialization of cities and the emergence of a post-industrial society, based on knowledge and information. Thus, while it's still thriving to put itself as a viable path for development, thereby promoting specific public policies, the field of creative economy intersects with others, such as the collaborative economy, to materialize initiatives that aim to give space for creative businesses, such as collaborative stores, which consist of shared spaces between different brands for the sale of their products, with the division of infrastructure costs in order to obtain more competitive conditions. Therefore, this study aims to identify and propose a comparative analysis of such collaborative stores, in terms of their management practices and challenges faced, based on the reality of three cities: Belém, Fortaleza and Rio de Janeiro. For this, the work is divided in two parts: the first with the theoretical framework about the origins and possibilities of classification of the fields of creative economy and collaborative economy, in addition to the concept adopted to the term collaborative management, and the second part with the field research, with a synthesis of the answers obtained after the interviews, which used a semi-structured script, with the people who manage such spaces and with the brands present in these collaborative stores.